Kepraktisan E-handout “Lingkungan Lahan Basah Sekitar” dalam Melatihkan Keterampilan Berpikir Kritis - Wahyunah Wahyunah; Atiek Winarti; Badruzsaufari Badruzsaufari (Program of Biology Education, Universitas Lambung Mangkurat, 2022)
Critical attitude is born from critical thinking skills in the neighborhood (surrounding environment) and the daily life of the individual. Critical thinking skills can be trained in the learning process by using appropriate learning strategies and resources. One of the learning resources that can be used to practice critical thinking skills is a contextual electronic handout (e-handout). This study aims to describe the practicality of the e-handout “Surrounding Wetlands Environment” to practice critical thinking skills. Assessment of the practicality of the e-handout through one-on-one evaluation and small group evaluation. The research subjects were 5 students of Biology Education at Universitas Lambung Mangkurat (one-on-one evaluation) and 5 other students (small group evaluation). The data collection instruments used were readability test questionnaires, implementation test questionnaires, student response questionnaires, and critical thinking skills measurement activity sheets. The results showed that the e-handout